ANALYSIS OF RED WATERMELON AND YELLOW WATERMELON FARMING (Case Study: Secanggang District, Langkat Regency) - Ahmad Riandy Harahap (Agripreneur : Jurnal Pertanian Agribisnis, 2021)
The purpose of this study was to determine the development of red watermelon and yellow watermelon in the last 5 years; to analyze the characteristics of red and yellow watermelon farmers; to analyze the income of red and yellow watermelons; to analyze the feasibility and to determine the effect of production factors on the acceptance of red watermelon and yellow watermelon. The data analysis method used is the income analysis method; R/C Ratio and B/C Ratio analysis methods; multiple regression analysis methods. From the results of the study, it was found that the production and area of ??red watermelon and yellow watermelon farming land continued to increase over the last 5 years; yellow watermelon farming income is greater than red watermelon farming income; Yellow watermelon farming is more feasible than red watermelon.